(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
The BCS Class II medication aceclofenac is poorly soluble in water and undergoes significant metabolism in human hepatocytes and microsomes. It has a 15% oral bioavailability, which is low. Piperine is a naturally occurring bioenhancer that is used to increase the oral bioavailability of many different medications. In this study, the pharmacokinetics of Aceclofenac (20 mg/kg) alone and in combination with Piperine (10 mg/kg) in rats were tested. Despite their distinct chemistry and physical properties, in this study, piperine was used to enhance the bioavailabilty of aceclofenac followed by the development and validation of HPLC method to determine their simultaneous measurment in rat plasma. Plasma samples were processed by solid phase extraction and subjected to HPLC analysis. The analysis identified retention time for Aceclofenac and piperine to be 5.3 and 14.4 minutes respectively. We found the linear concentration range of aceclofenac in rat plasma between 0.1 to 20 µg/mL. The correlation coefficient (R2) determined was 0.9995. Cmax was increased from 23.59 µg/mL to 48.52 µg/mL. By including piperine with aceclofenac in formulation, its oral bioavailability can be improved.